Take and Take: The Citizen-Taxpayer and the Rise of Democratic Colonialism in Canada - Gettler, Brian (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2021)
Tillotson’s Give and Take is a major contribution to Canadian history, a highly engaging analysis of culture and politics in the critical yet wildly understudied field of fiscal policy. The book makes the persuasive argument that the taxpayer was never somehow anathema to the citizen but rather that the two figures were mutually constitutive. After presenting a general overview of the Give and Take, this review considers its treatment of First Nations and taxation. While the book fruitfully covers the topic, the review argues that Tillotson might have used her material to profile not the rise of Canadian democracy but that of democratic colonialism in Canada.